Sponsorship in Sports on the Example of Croatian Basketball Clubs - Zdrilić, Ivica; Kevrić, Dino; Vrkić, Željko (Oeconomica Jadertina, 2017)
Sports sponsorship is one of the fastest growing forms of marketing communication and as such it is extremely attractive to many companies looking for a more efficient way of attracting customers. The article presents a theoretical review of literature, from sports marketing and sponsorship in a broader sense to sports sponsorship, its main forms as well as the positive and negative aspects related to it. It presents an overview of the status of sports sponsorship in the Republic of Croatia and its development after the economic crisis. What is emphasized in this article is the research of sponsorship in sports on the example of Croatian basketball clubs, which examines how much do clubs invest in their marketing and what are their strategies in the process of attracting sponsors. The research was conducted on Croatian male first-league basketball clubs, showing that they do not have the appropriate strategy when looking for sponsorships, or they do not address the issue appropriately.